2005
DOI: 10.1080/09548980500463982
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear and higher-order approaches to the encoding of natural scenes

Abstract: Linear operations can only partially exploit the statistical redundancies of natural scenes, and nonlinear operations are ubiquitous in visual cortex. However, neither the detailed function of the nonlinearities nor the higher-order image statistics are yet fully understood. We suggest that these complicated issues can not be tackled by one single approach, but require a range of methods, and the understanding of the crosslinks between the results. We consider three basic approaches: (i) State space descriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…Here we show that two-dimensional Hermite (TDH) filters, an orthogonal basis set with a high degree of symmetry, simplify the description of high-order statistics of natural images, both locally and over wide areas. The significance of this result is that high-order statistics carry the local features that distinguish natural images from Gaussian processes [3, 8, 17, 18, 29], but they are challenging to analyze because of their high dimensionality. By identifying a hidden symmetry in high-order statistics, TDH functions provide a kind of dimensional reduction, and therefore, a needed simplification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we show that two-dimensional Hermite (TDH) filters, an orthogonal basis set with a high degree of symmetry, simplify the description of high-order statistics of natural images, both locally and over wide areas. The significance of this result is that high-order statistics carry the local features that distinguish natural images from Gaussian processes [3, 8, 17, 18, 29], but they are challenging to analyze because of their high dimensionality. By identifying a hidden symmetry in high-order statistics, TDH functions provide a kind of dimensional reduction, and therefore, a needed simplification.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, [3] showed that this could be used to distinguish natural images from synthetic ones (including realistic computer-generated scenes), by applying linear classifiers to a feature space of wavelet coefficients. Other investigators have also used wavelet coefficients as a starting point, but focused on the extent to which wavelet coefficients are independent [17, 18]. Thus, the filter approach provides a useful characterization of natural image statistics -- but even with a filter-based approach, the number of parameters required to describe high-order image statistics is still large.…”
Section: Introductionmentioning
confidence: 99%
“…These features are of high perceptual relevance for object recognition (Attneave 1954, Mackworth and Morandi 1967, Biederman 1987. The extraction of these features can be provided by non-linear i2D-selective operators , which mimic the operations of nonlinear neurons in the visual cortex (Shapley 2004;Zetzsche and Nuding 2005). Figure 4 shows examples of these nonlinear sensory features.…”
Section: Sensorimotor Featuresmentioning
confidence: 98%
“…This geometric distribution of responses can then be understood in accordance with the distribution of images that have been projected to different encoding spaces (such as those defined by visual filter outputs). This general approach has been used in theories of sparse coding [29] and the non-linear behavior of visual neurons [30][31]. By focusing on the full state-space geometry of the responses produced by an evoked potential (rather than simple features of the response), our experiments will show that it is possible to provide both a rational model of the signal as well as to provide an estimate of the information carried by that signal.…”
Section: Introductionmentioning
confidence: 99%